(untitled) (Veterinary Science, 2017)
In the present work, the electrical conductivity (conductivity specifies) of the synovial fluid of healthy bovines, to temperatures between 20 ºC and 40 ºC +/- 0,1 ºC, taking place intervals of 5 ºC, has been an strong linear dependency, between the electrical conductivity and the temperature which pending bond. The value of the specific conductivity at average temperature, from graphical interpolation of this animal (38,5 ºC is: K 10/2= 1,66 +/- 0,02 0hm-1 cm-1, where K is electrical conductivity. The energy of activation Ea, of the studied procces is obtained by means of the graphical representation of Log K in function of the inverse one of the absolute temperature, according to which it establishes the equation of Arrhenius. The obtained value for Ea is 2,4 +/- 0,2 Kcal Mol ^1.